Braving the Waves: The Role of Time and Risk Preferences in Illegal Migration from Senegal - Jean-Louis L. Arcand; Linguère Mously Mbaye (Institute for the Study of Labor (IZA), 2013)
This paper aims to provide the first evidence concerning the relationship between time and risk preferences and illegal migration in an African context. Based upon our theoretical model and using a unique data set on potential migrants collected in urban Senegal, we evaluate a measure of time and risk preferences through the individual's intertemporal discount rate and coefficient of absolute risk aversion. Remarkably, our results show that these individual preferences matter in the willingness to migrate illegally and to pay a smuggler.
Keywords: F22; O15; O16; R23; 330; illegal migration; discount rate; risk aversion; Africa; Senegal